Antibioticoterapia para o tratamento de periotonite em diálise peritoneal: redicão sostemática de estudo clínicos controlados e série de casos - Pinotti, Douglas Gonçalves [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The choice of antimicrobials for treatment of peritoneal dialysis (PD)-related peritonitis is crucial for a favorable outcome. There is no consensus about the best therapy; few prospective controlled studies have been published, and the only published systematic reviews did not report superiority of any class of antimicrobials. The objective of this review was to analyze the results of PD peritonitis treatment in adult patients by employing two methodologies, the systematic review with meta-analysis of randomized clinical trials (RCT) and the proportional meta-analysis of cases series, a new strategy that has been used in other clinical settings. Methods: A review of the literature was conducted. There was no language restriction. Studies were obtained from MEDLINE, EMBASE, and LILACS. The inclusion criteria were: (1) case series and RCTs with the number of reported patients in each study greater than five, (2) use of any antibiotic therapy for initial treatment of PD-related peritonitis (e.g., cefazolin plus gentamicin, vancomycin plus gentamicin), for gram-positive (e.g., vancomycin, first generation cephalosporin), or for gram-negative rods (e.g., gentamicin, ceftazidime, fluoroquinolone), and (3) studies specifying the rates of resolution. For RCT analyses the outcomes resolution, primary response, catheter removal, and relapse were considered, whilefor proportional meta-analysis only the outcome resolution rate was taken using a random-effects model, and the pooled resolution rates were calculated. Results: 64 studies (21 RCT and 43 case series) met all inclusion criteria. There were 21 comparisons between the antibiotics using in RCT. No superior antimicrobial class or associations were identified, when used for empirical treatment or for gram-positive or gram-negative episodes. Among the case series the pooled resolution rate of ceftazidime plus glycopeptide as initial treatment (pooled propor = ...

A escolha do regime antimicrobiano para o tratamento das peritonites em Diálise Peritoneal (DP) é fundamental para uma evolução clinica favorável. Não há consenso sobre a melhor terapia; poucos estudos prospectivos controlados foram publicados e a única revisão sistemática com meta-análise disponível não mostrou superioridade de alguma classe ou associação antimicrobiana. O objetivo desta revisão foi analisar os resultados do tratamento das peritonites em adultos em DP empregando duas metodologias, revisão sistemática com meta-análise de estudos clínicos randomizados (ECR) e a meta-análise proporcional de série de casos, uma nova estratégia que tem sido utilizada em outras condições clinicas. Método: Foi realizada uma revisão de literatura, sem restrição de idioma. Os estudos foram obtidos das bases CENTRAL, MEDLINE, EMBASE e LILACS. Os critérios de inclusão foram: (1) ECR e série de casos com número de pacientes em cada estudo maior que cinco (2) uso de algum antibiótico, ou esquema antibiótico para tratamento inicial de peritonite em DP (ex: cefazolina/gentamicina, vancomicina/gentamicina); para germes gram-positivos (ex:vancomicina/cefalosporina da primeira geração) e para gram-negativos (ex: gentamicina, ceftazidima e fluoquinonolonas) (3) estudos relatando a taxa de resolução. Para os ECR foram considerados os desfechos cura, resposta primária, remoção de cateter e recidiva epara metanálise proporcional de serie de casos foi considerado apenas o desfecho percentagem de cura. Resultados:Um total de 65 estudos (22 ECR e 43 série de casos) preencheram os critérios de inclusão. Nos RCT não foi observada superioridade de nenhuma classe ou associação antimicrobianautilizada para tratamento empírico ou para episódios causados por germes gram-positivos ou negativos. Entre as serie de casos, a associação ceftazidina/glicopeptídeo (proporção total= 87% [IC 95% = 0,83-0,91] ) apresentou...
Keywords: Dialise peritoneal; Peritonite - Revisão; Microbiologia médica; Meta-analises; Medical microbiology